2014
DOI: 10.4238/2014.february.27.6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of +2836 G>A in the apoE gene are strongly associated with the susceptibility to essential hypertension in the Chinese Hui population

Abstract: ABSTRACT. In the present study, the correlation of polymorphisms of the apolipoprotein E (apoE) gene with the susceptibility of essential hypertension (EH) was investigated. Single nucleotide polymorphisms of the apoE gene at the -491 A>T, +969 C>G, and +2836 G>A sites were determined in 221 non-EH individuals and 109 subjects with EH of Chinese Hui ethnicity using polymerase chain reaction-restriction fragment length polymorphism analysis. The results showed that neither the genotypic frequency nor the alleli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Utermann et al . [ 33 ] first reported that the presence of APOE polymorphisms has inspired widespread interest in the genetic associations between these single-nucleotide polymorphisms and many complex diseases including Alzheimer's disease,[ 34 ] type 2 diabetes,[ 35 ] hypertension,[ 36 ] and others. Besides, several studies have provided evidence that APOE is functional.…”
Section: Discussionmentioning
confidence: 99%
“…Utermann et al . [ 33 ] first reported that the presence of APOE polymorphisms has inspired widespread interest in the genetic associations between these single-nucleotide polymorphisms and many complex diseases including Alzheimer's disease,[ 34 ] type 2 diabetes,[ 35 ] hypertension,[ 36 ] and others. Besides, several studies have provided evidence that APOE is functional.…”
Section: Discussionmentioning
confidence: 99%
“…And studies have shown that the polymorphism at the +2836 G>A site in the apoE gene is strongly correlated with the susceptibility to essential HTN in Hui people. [11] In addition, Hui people believe in Islam. Due to religious beliefs, they do not eat pork in their diet, mainly beef and mutton.…”
Section: Introductionmentioning
confidence: 99%
“…Hui people's genetic background, living environment, eating habits, religious belief, ethnic customs, and other factors are different from other population of China. And studies have shown that the polymorphism at the +2836 G>A site in the apoE gene is strongly correlated with the susceptibility to essential HTN in Hui people [11] . In addition, Hui people believe in Islam.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the common APOE polymorphisms, other polymorphisms of APOE have also been reported in this relationship. APOE + 2836G>A polymorphism is associated with the susceptibility to hypertension [ 50 ]. An animal study has shown that the pathogenesis of hypertension in ApoE(−/−)/Cyp1b1(+/+) mice fed a high-fat diet is most likely due to oxidative stress caused by CYP1B1, as well as increased plasma lipid levels [ 51 ].…”
Section: Discussionmentioning
confidence: 99%